Livestock water needs in pastoral Africa in relation to climate and forage - King, J.M. (International Livestock Centre for Africa, 1983)
Discusses livestock water needs and the variation of water dependence in dif. circumstance, mentioning body water functions; physiological aspects of water balance; channels of gain & loss; and factors affecting water balance, particularly energy production, thermoregulation and water availability. Examines energy and water use, as well as water & livestock development in pastoral areas of Africa.